Fundamentos filosóficos y jurídicos de la tolerancia religiosa en Europa (siglos xvi-xviii) : el camino hacia la libertad - José Ignacio Solar Cayón (Mélanges de la Casa de Velázquez)
Toleration is a historical concept whose meaning varies depending on the context and on the issues concerned. This article specifically examines the basic elements of the notion of religious toleration as they developed following the breakdown of Christian unity in 16th-century Europe. In this context, the debate on toleration was the first manifestation of philosophy’s concern for the limits of legitimate action by political power, and marked the beginning of a process of assertion of individual autonomy which would eventually culminate in the idea of religious freedom as a natural right. Nevertheless, an analysis of the various political and religious groups driving that process reveals the different roots, philosophies and values underlying each of these notions, and also the complexity of the relations between them.